2021
DOI: 10.1016/j.ijppaw.2021.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and diversity of Sarcocystidae protozoa in muscle and brain tissues of bats from São Paulo state, Brazil

Abstract: Studies on infectious and emerging diseases caused by bats have been increasing worldwide due to their well-recognised status as a reservoir species for various infectious agents as well as their close relationship to humans and animals. This study reports the molecular frequency and diversity of the parasites belonging to the Sarcocystidae family in bats in São Paulo state, Brazil. A total of 2892 tissue samples (brain and pectoral muscle/heart homogenates) from 1921 bats belonging to 36 species were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…from our study concurs with what would be expected considering their feeding behavior, since they are strictly insectivorous species [21]. In contrast, previous serological and molecular studies have evidenced high rates of T. gondii infection in insectivorous bats [15] and multiple risk factors, other than trophic sources, have been proposed: different ecological traits of bat species (gregariousness, dietary habits), environmental conditions and density of oocysts in the environment [1,14,16,27,28]. The present is the third study focused on the presence of T. gondii in insectivorous bats performed in Europe.…”
Section: Discussionsupporting
confidence: 90%
“…from our study concurs with what would be expected considering their feeding behavior, since they are strictly insectivorous species [21]. In contrast, previous serological and molecular studies have evidenced high rates of T. gondii infection in insectivorous bats [15] and multiple risk factors, other than trophic sources, have been proposed: different ecological traits of bat species (gregariousness, dietary habits), environmental conditions and density of oocysts in the environment [1,14,16,27,28]. The present is the third study focused on the presence of T. gondii in insectivorous bats performed in Europe.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of H. hammondi remains undisclosed in both definitive and intermediate hosts. Only few research reported the sporadically presence of H. hammondi in cat and dog faeces ( Schares et al, 2005 , 2008 ; Dubey et al, 2013 ) and in intermediate host tissues ( Cabral et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genera Toxoplasma (22.7%, 10/44) and Sarcocystis (11.4%, 5/44) were reported in wild free-ranging birds rescued in the state of Minas Gerais ( Rêgo et al, 2021 ). Another study has shown 4.7% (91/1921) of bats with tissues positive for the 18S rDNA gene were detected, and eight genera of protozoa of the Sarcocystidae family ( Besnoitia, Cystoisospora, Hammondia, Hyaloklossia, Neospora, Nephroisospora, Sarcocystis , and Toxoplasma ) were identified in 50 samples of 16 bat species (belonging to the families Phyllostomidae, Molossidae, and Vespertilionidae) in the state of São Paulo ( Cabral et al, 2021 ). In addition, Ludwig et al (2021) detected the 18S rDNA gene in brain and heart tissue from six brown howler monkey ( Alouatta guariba clamitans ) and identified the genus Sarcocystis (4/6) and Toxoplasma (2/6).…”
Section: Discussionmentioning
confidence: 99%